Text and Terror: How Boko-Haram Terrifies Nigerians Using Ordinary Words - OMOLADE BAMIGBOYE (Journal of Language and Literature, 2020)
This paper investigates how Boko-Haram uses language to create terror in the minds of Nigerians. Boko-Haram, an Islamic terrorist organisation based in Nigeria and some other West African countries, periodically releases videos in which threats are made to the public. These videos are then transcribed into text by major news media all over the world. The thesis of the paper is if seemingly innocuous expressions are interpreted with fear as a result of who utters them. After a thorough study of possible theoretical approaches, the cognitive stylistics approach was deemed most suited for the present work. This is because the approach sees readers as actively involved in the process of meaning-making, Jeffries and McIntyre (2010: 127). Using the Schema Theory as conceptual framework, I argue that the readers of these statements interpret same with the residual knowledge they have of the world. Schema Theory submits that certain elements of background knowledge are superimposed on the text by the reader in creating a world (scenario) while reading the text. The findings reveal that the source of a text goes a long way in determining how it is digested by readers. Also, readers make sense of texts based not just on what is read, but the surrounding information they mentally impose on it.